Kualitas Pelayanan Program Prioritas Nasional Percepatan Pendaftaran Tanah Sistematis Lengkap - Andi Patta Yusuf; Albertus Yosep Maturan; Dapot Pardamean Saragih (SOCIETAS, 2020)
The certificate service process has problems.The research objectives explain how the quality of publicservice.Qualitative research methods.Primary and secondary data sources.Data collectiontechniques; Observations, interviews, documentation and poll questions.Data analysis techniques;Reduction, presentation, verification or conclusion.Research results, First Process-Related quality ofpublic service shows good process effort but not maximally due to the interconnectedness of theprocess are still many problems that arise as a complex problem, Both Outcomes-Relatedimplementation PTSL applied based on the service system No.1 the year 2010 about standards ofservice and land arrangement by human resources of each task and responsibility for the workload,some of the SDM has a knowledge directly proportional to his education, such as educated SD,SMA/SMK, D1, D3, D4, and S1.Some SDM conditions have not demonstrated professionalism in whichthere are problems of the, Third Image-Related service is trusted to inform the implementation of PTSLstarting in January 2019 precisely in the land office and each village opened to the public for us toreceive a target land bid as many as 6,800 land fields, but For Land Fields Map (PBT) amounted to1,500 fields and the other 5,300 land areas are certified one includes Merauke regency.The publictrust is full of pique with what inconsistency is promised timeliness Issuance of delayed certificatesexperienced protracted applicants until the end of the year 2019 there has been no point of clarity.